Customer Satisfaction On E-Banking Service Quality In Malaysia - Kah Boon Lim; Sook Fern Yeo; Yen Nee Tey; Cheng Ling Tan (Research Synergy Foundation, 2023)
Rapid technology developments and the advance in the digital economy created good value for electronic banking. Online banking which is also known as e-banking becomes essential in year 2020 due to Covid outbreaks which can reduce the customer and employee interface and ensure all the transactions can continue conducting with cashless. Consequently, e-banking has become popular with the purpose to continue routine transactions such as paying bills, top up, online transfer to others or for shopping purposes. Apart from that, customer satisfaction is also important to the success of businesses which can reduce the customer losses. With high customer satisfaction also can increase customer loyalty and directly can generate more revenue. The main purpose of this research is to study the factor influencing customer satisfaction on e-banking service quality in Malaysia. This research has included five independent variables which included efficiency, website design, security or privacy, reliability, and responsiveness.to explain the customer satisfaction towards E-banking services. A minimum of 138 target respondents will be interviewed by a set of questionnaires via Google Form. The data collected were then keyed into the SPSS software and further analysed by using the Smart PLS software. The analysis result revealed that all independent variables except efficiency were found to have significant relationship to influence customer satisfaction towards E-banking services. This research study was important to the banking sector and for those other researchers that are interested in this topic research.